Educational Leadership at District Level: Women’s Reflections on Their Self-Perceptions - Kutu, Mercy; Zulu, Connie (Alberta Journal of Educational Research, 2022)
Self-perception constitutes an indispensable component of social life that might significantly contribute to one’s leadership ability. This study examined the perceptions that women in educational leadership at the district offices in one of the provinces in South Africa have about themselves and their leadership roles. It formed part of qualitative research aimed at exploring women’s experiences of career advancement into educational leadership positions at the district level in the North West Province of South Africa. The aim was to understand how district office women see themselves and their leadership responsibilities, as well as how they believe their own self-perceptions have helped them advance in their careers. The participants for this study were thirteen female managers in educational leadership positions who were selected using the purposive sampling method. Framework and thematic analysis methods were utilized in the analysis of the individual face-to-face interviews. The study adopted the self-concept theory as its core theoretical framework. The study revealed that women in educational leadership perceived themselves as competent and accomplished leaders who possessed the requisite leadership qualities to enable them to progress in their careers. The study's findings also demonstrated that women's self-perceptions and educational leadership capabilities have a substantial impact on their careers, as they serve as sources of motivation and propelling forces for advancement. Keywords: Self-concept, self-perceptions, educational leadership, career advancement La perception de soi est une composante indispensable de la vie sociale qui peut contribuer de manière significative à la capacité de leadership d'une personne. La présente étude examine les perceptions qu’ont les femmes qui occupent des postes de responsabilité dans le domaine de l'éducation dans l'une des provinces d'Afrique du Sud d'elles-mêmes et de leurs rôles en tant que leaders. Elle s'inscrit dans le cadre d'une étude qualitative plus large visant à explorer les expériences des femmes en matière d'avancement professionnel à des postes de direction dans le domaine éducatif au niveau du district dans la province du Nord-Ouest de l'Afrique du Sud. L'objectif était de comprendre la perception qu’ont les femmes des services publics du district de leurs responsabilités de leaders et de la manière qu’elles pensent que leur propre perception de soi les a aidées à progresser dans leur carrière. Les participantes à cette étude étaient treize femmes cadres occupant des postes de responsabilité dans le domaine de l'éducation, sélectionnées par la méthode de l'échantillonnage raisonné. Les méthodes d’analyse du cadre et d'analyse thématique ont été utilisées pour les entretiens individuels en présentiel. L'étude a adopté la théorie de l’image de soi comme cadre théorique de base. L'étude a révélé que les femmes ayant des responsabilités dans l'éducation se perçoivent comme des leaders compétents et accomplis qui possèdent les qualités de leadership requises pour leur permettre de progresser dans leur carrière. Les résultats de l'étude ont également démontré que la perception que les femmes ont d'elles-mêmes et de leurs capacités de leadership en matière d'éducation a un impact considérable sur leur carrière, car elle constitue une source de motivation et un encouragement à avancer. Mots clés : Image de soi, perception de soi, leadership éducatif, avancement de carrière